(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Child Sexual Abuse (CSA) is a serious public health problem with serious psychological, social, and legal consequences for the victims. This systematic review synthesizes and combines the literature to determine the combined effect of CSA on the individual. Psychological effects encompass increased vulnerability to mental illness, including depression, anxiety, and post-traumatic stress disorder (PTSD); social effects tend to maximize alienation, restrict the establishment of relationships, and increase stigma; and legal issues highlight barriers to reporting abuse and accessing the justice system. Referring to a comprehensive examination of research on primary predictors and deterrents of CSA, the review then goes on to outline how influences cutting across demographics—age, gender, socio-economic status, and culture—multiply these effects. Case studies outline the multi-faceted character of the impact of CSA and underscore the need for a multi-dimensional recovery process. Recommendations for expanding psychological counselling services, fortifying social support systems, and development of legal codes to construct a survivor-based system of justice are made. The results stress working together between policymakers, mental health professionals, teachers, and law enforcement agents to create an assisting environment for CSA survivors.